Draft Annual Plan for 1968-69 Government of Maharashtra - Planning Commission (Planning Commission, 1968)
In order to make the State self sufficient in food grains the State Government has launched on the Scheme of high yielding varieties programme since the year 1966-67 During that year an area of 7.56 lakhs areas was covered with high yielding varieties of Taichung Paddy and Mixed wheat (1 lakh acre each), Hybrid Jowar irrigated (3.50 lakh - acres) Hybrid bajra.
Government of Maharashtra, Finance Department (Planning)